Quality Management Systems and Models as a Tool for Small and Medium Enterprieses Development and Competitiveness Increase - ZANE DRIŅĶE; ROSITA ZVIRGZDINA (Communications of International Proceedings, 2020)
The theme "Quality management system and models as a tool for small and medium enterprieses development and competitiveness increase" is determined by the basic concepts included in the topic - small and medium enterprises (hereinafter referred to as "SMEs"); competitiveness and quality management system (hereinafter referred to as “QMS”). Small and medium-sized enterprises are interested in producing products in which potential buyers can see the qualitative features they need to meet their needs. Thus, the merchant, the quality requirements and competitiveness of the product produced by him coalesce into one system whose function is closely related to the goal of the product buyer to more fully meet their needs. Today, the European Economic System employs more than 23 million small and medium-sized enterprises, which produce goods and services worth more than 4 billion Euros. These companies employ over 90 million economically active people from different European countries (Eurostat, 2018). Object and object of the research: the following object of the research is determined: competitiveness of small and medium enterprises and the subject of this research: improvement of the competitiveness of small and medium enterprises by applying the conformity requirements defined by the quality management system. The purpose and tasks of the research: to reveal the positive effects of the implementation of the quality management system on increasing the competitiveness of small and medium enterprises, as well as to identify the most important barriers to the restructuring of production in accordance with the requirements of the quality management system for small and medium enterprises in the local economy. The following main tasks are identified for achieving the goal: explain the most important concepts of the work theme; create a model for interconversion and interaction between customers' quality requirements and production conformity requirements. Research Hypothesis: elements of the quality management system applied to increase the competitiveness of SMEs can lead to a competitive advantage in the market. Research methodology and methods: the study uses analysis and synthesis methods, deductions and induction methods as well as logical approach methods. However, appropriate quantitative methods are used to process the data obtained. Result of the research: in the course of the research a model is developed and recommendations for implementation of the quality management system in enterprises are worked out.
Keywords: small and medium-sized enterprises; competitiveness; quality management system; management; competition; national economy